Accelerated Silverlight 2 - Scanlon, Jeff. (Apress, 2009)
Accelerated Silverlight 2 will get you up to speed with version 2 of Silverlight quickly and efficiently. Author Jeff Scanlon assumes youre already comfortable with the basics of .NET coding and with Windows Presentation Foundation (WPF), and helps you build on your existing knowledge to make your journey to Silverlight 2 proficiency as quick and painless as possible. Where coding techniques are similar to other, more established areas of .NET, he'll say so. Likewise, where theres a syntax or conceptual gotcha that youre existing coding habits will walk you into, hell point that out, too. Youll find fasttrack coverage of all the most important elements of the Silverlight 2 technology ranging from XAML to standard controls, from dealing with media to networking, from testing to deployment. Two fully-worked sample applications conclude your path to Silverlight 2 mastery because nothing reinforces your understanding of how concepts fit together as much as looking at finished code. The book is based on the assumption that readers will already be very comfortable with the workings of the .NET Framework. Knowledge of Expression Blend is useful, but the author doesnt assume that youre a master of it. Youll learn the Blend techniques that you need to know as you go along. By the end of the book, the author will have provided you with a sound, concise, path to mastery of Silverlight 2.